APLIKASI KOMPRESI FILE AUDIO MENGGUNAKAN ALGORITMA ARITHMETIC CODING - Annisa Diah Mutiara; Sutardi Sutardi; Rahmat Ramadhan (semanTIK, 2016)
The process of data compression based on the fact that in almost all types of data are always there repetition in the data component has, for example, in a text sentence there will be redundancies letter alphabet of letters ܽ  through  ݖ. Compression of data through the encoding process seeks to eliminate the element of repetition  by  changing  it such that the data size becomes smaller. In this study, an audio  file  compression applications  is  making  by  using  Arithmetic Coding  algorithm. Unified Modelling Language (UML)  is used as system development tools. In making this application is emphasized to compress the audio file extension * .wav.  Compression application testing is done by examining the  files that have different sizes with a sample  rate and bitrate values are the same. It was concluded that the audio  file with a large size takes longer to perform the compression process. The compressed audio  files can not be executed before passing the decompression process that caused a change in the structure of the current audio file decompression process. Keywords—Compression, File Audio, Arithmetic Coding